1. x^2 * x^6 = x^(2+6) = x^8
2. x^3 * x * x^8 = x^(3+1+8) = x^12
3. x^4 * x^3 * x^10 = x^(4+3+10) = x^17
4. 6x^2 * 2x^5 = (6*2) * (x^2 * x^5) = 12x^(2+5) = 12x^7
5. When we multiply like bases, we add the exponents to account for the repeated multiplication. For example, x^2 * x^3 = x^(2+3) = x^5. This is because we are multiplying x * x * x * x * x, which is x^5.
5 Problems - SHOW ALL WORK!
1 . x^2 * x^6 =
2 . x^3 * x* x^8 =
3 . x^4*x^3*x^10=
4 . 6x^2* 2x^5=
5 . Why do we add exponents when we are multiplying like bases?
1 answer